Hubungan Antara Screen Time dengan Angka Kejadian Miopia Pada Anak Sebelum dan Setelah Masa Pandemi Covid-19 : Sebuah Tinjauan Pustaka - Anugrahsari, Santi; Shania Audrianisa; Cahya Virgin Septyany; Appy, Enjeline Grecielya; Rohy, Charlos Ivanly Jusuf (Universitas Kristen Krida Wacana, 2024)
The COVID-19 pandemic policies, outdoor activity restrictions, and distance learning have significantly impacted the occurrence of myopia in children. These changes are associated with increased screen time, decreased outdoor activities, and insufficient sleep duration, indicating potential long-term effects on myopia prevalence and development. This literature review utilizes articles from research journal databases searched through the internet. The internet databases used include Google Scholar and PubMed, using keywords: